Penerapan Pemikiran Ibnu Miskawaih Sebagai Sumber Belajar Pendidikan Aqidah - Muhammad Akbar Khan; M. Reza Pahlevi; Alaika M. Bagus Kurnia PS (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2022)
This research aims to learn and understand the application of the thought of a philosopher named Ibnu Miskawih as a source of learning and education, aqidah. Education itself has a very broad meaning, but here education has the meaning of a change of system for the better. Education can always change to any side, and aqidah is the basic beliefs or fundamental beliefs of the religion followed by man. Often, there is denial against it in the name of education and aqidah, which starts with the debate and controversy about the teaching of education. Ibnu Miskawih is a Muslim philosopher, and he has made a great contribution to Muslim education, especially in the realm of Aqidah. This thought is adopted for the purposes of research, where man, with his mind, is able to survive and determine what should be done and obliged to be left. The fruit of the thought of Ibnu Miskawih is more focused on man and education, Aqidah, where this aqidah is the way to God, even more in this modern era, which indirectly results in a small number of shifts in Aqidah.